Prediction of the Development of Depression in Patients with Autoimmune Thyroiditis and Hypothyroidism - Kamyshna, Iryna; Pavlovych, Larysa; Kamyshnyi, Alexandr M. (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Hypothyroidism is frequently accompanied by depression symptoms, whereas depression is considered the most common mental disorder. AIM: It is crucial to analyze the associations of the brain neurotrophic factor (BDNF) gene polymorphism (rs6265), the VDR gene polymorphism (rs2228570), and the NMDA gene polymorphism (rs4880213) with the depression in patients with autoimmune thyroiditis and hypothyroidism in the Western Ukrainian population and predict the development of depressive disorders in these patients. METHODS: The study involved a total of 153 patients with various forms of thyroid pathology. BDNF levels in the sera of the patients and healthy individuals were quantified using enzyme-linked immunosorbent assay with highly sensitive Human BDNF ELISA Kit (Elabscience®, United States, Catalog No: E-EL-H0010) on E.I.A. Reader Sirio S (Seac, Italy). Genotyping of the VDR (rs2228570), BDNF (rs6265), and NMDA (rs4880213) gene polymorphism using TaqMan probes and TaqMan Genotyping Master Mix (4371355) on CFX96™Real-Time Polymerase chain reaction (PCR) Detection System (Bio-Rad Laboratories, Inc., USA). PCR for TaqMan genotyping was carried out according to the kit instructions (Applied Biosystems, USA). We used the Student’s t-test, ANOVA, Pearson’s Chi-square test, ROC-analysis, odds ratio test, relative odds ratio test. The odds ratio and 95% confidence interval were computed by binary logistic regression. RESULTS: When comparing the presence of depression on the Hamilton scale, statistically significant differences were found depending on BDNF gene polymorphism (rs6265) (p < 0.001), and non-statistically noticeable differences were detected depending on the VDR gene polymorphism (rs2228570) and NMDA gene polymorphism (rs4880213). Our study revealed a marked inverse connection between depression and BDNF levels (p < 0.001) and a reverse moderate correlation between depression and fT4 (p < 0.001) and 25-OH Vitamin D levels (p < 0.001). In addition, we identified a direct moderate correlation between pronounced levels of depression and thyroid-stimulating hormone (TSH) in the blood (p < 0.001). CONCLUSIONS: Indicators such as BDNF, TSH, fT4, anti-TPO, and 25-OH Vitamin D levels were found to be prognostically significant criteria for the risk of developing depression.